Bacterial Resistance: a new scientific challenge - Rodríguez-López, Julián (2021)
The discovery of antibiotics in the 19th century allowed to treat infectious diseases that to date were incurable. However, nowadays, the number of resistant bacteria has grown remarkably, placing the problem of bacterial resistance as one of the main causes of mortalities worldwide. This work addresses the origin of this phenomenon and the possible solutions that are proposed to minimize its effects.